The effect of transcatheter edge-to-edge repair on right ventricular reverse remodeling in patients with severe tricuspid regurgitation - Tang, Y R; Chen, X; Wang, B; Su, M L; Chen, X; Gao, Q M; Huang, X Y; Yao, Y E; Wang, Y (Zhōnghuá xīnxuèguănbìng zázhi, 2025)
To quantitatively analyze right ventricular reverse remodeling in patients with severe tricuspid regurgitation after transcatheter tricuspid edge-to-edge repair (T-TEER) by two-dimensional speckle tracking echocardiography, and to preliminarily evaluate the clinical efficacy of this procedure. This study was a prospective single-center cohort study. Patients diagnosed with severe tricuspid regurgitation at the Xiamen Cardiovascular Hospital Xiamen University from March 2021 to June 2023 were enrolled. All patients underwent transthoracic echocardiography and transesophageal three-dimensional echocardiography before T-TEER, and transthoracic echocardiography at 30 days, 6 months, and 9 months after T-TEER. The primary endpoint was major adverse cardiovascular and cerebrovascular events, including death, stroke, myocardial infarction, reoperation, arrhythmia, and conduction block. Other clinical evaluation indicators included New York Heart Association (NYHA) functional classification and tricuspid regurgitatio